Connecting Macroscopic, Molecular, and Symbolic Representations with Immersive Technologies in High School Chemistry: The Case of Redox Reactions - Lu Wang; Georgia Hodges; Juyeon Lee (MDPI AG, 2022)
Redox reaction is a difficult concept to teach and learn in chemistry courses at the secondary level. Although the significance of connecting macroscopic, molecular, and symbolic levels of representation has been emphasized in the chemistry education literature, most redox instruction involves only macroscopic and symbolic representations. To address this challenge, we designed a blended-reality immersive environment (BRE) model, which blends a traditional experiment with immersive technologies to make the molecular representations of redox reactions visible. The effectiveness of this model in supporting students' learning of redox reactions was first reported in a different article. In this paper, we further explore the features of BRE that drive learning gains. Results from six high school classes in the U.S. with 351 students indicate that integrating the molecular representation through adding the chemical bonds concept facilitates students in making connections between macroscopic and symbolic levels to promote learning. Dynamic demonstrations of electrons' interaction with particles support students' understanding of the nature of redox reactions. This study shows the promise of adopting immersive technologies to present all three representations of chemistry concepts in one learning model.